Urgensi Penerapan Manajemen Konflik dalam Organisasi Perkuliahan - Maritsa Hariyanti; Guitari Dwi Rengganis; Fawaida Ilmalmaula; Faisal Rahman; Asyrof Abidin; Mu’allimin Mu’allimin (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
The purpose of this study is to investigate how urgent it is for higher education institutions to adopt conflict management practices. Conflicts in the workplace are often caused by different perceptions, so it is very important to manage them effectively. In this study, participants from higher education organizations at a private university in Yogyakarta participated in interviews using descriptive qualitative methodology. The findings of the study indicate that conflict management can be beneficial for business in addition to being important for preventing losses. Effective problem solving is a sign of successful conflict management, where the ability of individuals to communicate effectively under the direction of a capable leader is essential to achieving common goals. Awareness of problems and conflict resolution skills can improve outcomes and strengthen companies in the face of adversity. This study confirms that the implementation of effective conflict management is essential for the development of higher education organizations.